MENINGKATKAN PERMAINAN BOLA BASKET MELALUI MODEL PEMBELAJARAN BERMAIN LEMPAR SASARAN SISWA KELAS V SD NEGERI 01 SAMONGKEC. ULUJAMI KAB. PEMALANG TAHUN AJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This watchfulness aim detects enhanced know-how throw in basketball ball game in class student v sd country01 samong district ulujami pemalang year 2012/2013. Watchfulness kind class action watchfulness (PTK),watchfulness subject that used class student v sdn 01 samong that number 30 students. instrument that used testinstrument and observation sheet. data analysis that used that is qualitative descriptive analysis. Based onwatchfulness result and discussion, knowable technique play to throw target in uplift skill to throw inbasketball ball game in class student v sd country 01 samong district ulujami pemalang year 2012/2013, asfollows: a) stage pre study repair cycle from 30 class students v found 15 students that complete learn or as bigas 50 % and 15 students or 50 % student not yet complete learn. b) study repair stage in my cycle is found 9student from 30 student or 30 % student not yet complete learn, and 21 students or as big as 70 % thatcomplete learn. c) study repair stage in cycle ii found 2 student or as big as 6,6% that get value less than 70 and28 students or as big as 93,4 % complete learn. From watchfulness result be be concluded study model play tothrow target can increase basketball ball game in class student v sd.